E-Resources: The Millennium Users’ Expectations - Prafulla, Andhe; Chowdappa, N. (Journal of Information and Knowledge, 2020)
This paper highlights the link between the fifth law of library science "library/information is a growing organism” and the third law" every book/e-resource its reader/user", referring to user expectations. User expectations are growing and the reader/user" is lost between the mountain of information requiring changes in Library services and resources.